2016
DOI: 10.1080/15438627.2016.1258638
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 8 months of whole-body vibration training on quality of life in elderly women

Abstract: Whole-body vibration (WBV) training in elderly may improve muscle strength, muscle power and postural control. However, knowledge about the effect of WBV training in elderly on measures of health as a multidimensional construct (health-related quality of life, HRQoL) is scarce. The present study aimed to determine the effects of WBV training on HRQoL in elderly women. A total of 37 women (aged 82.4 ± 5.7 years) were recruited and were assigned to either the WBV group or to the control (CON) group. After 8 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…The effects of WBV training on quality of life and foot health in people with T2DM have been poorly studied. Regarding quality of life, previous studies showed that WBV could improve the quality of life in older populations [45] and other chronic conditions [46,47]. In this regard, a previous study of 6 weeks of WBV improved all domains (pain, general and mental health, vitality, physical, emotional, and social functioning) of the SF-36 quality of life questionnaire in people with diabetic neuropathy.…”
Section: Discussionmentioning
confidence: 92%
“…The effects of WBV training on quality of life and foot health in people with T2DM have been poorly studied. Regarding quality of life, previous studies showed that WBV could improve the quality of life in older populations [45] and other chronic conditions [46,47]. In this regard, a previous study of 6 weeks of WBV improved all domains (pain, general and mental health, vitality, physical, emotional, and social functioning) of the SF-36 quality of life questionnaire in people with diabetic neuropathy.…”
Section: Discussionmentioning
confidence: 92%
“…All of them, in some way, interfere with or affect the development or perception of quality of life and subjective wellbeing of older seniors. Among them, it is possible to mention: VO 2 max (Sillanpää et al, 2012), functional capacity (Wanderley et al, 2013), self-motivation (Solberg et al, 2014), restricted feeding practices (diets) and reduction of body weight (Napoli et al, 2014), social interaction (Fisken et al, 2015;Sales et al, 2015), food supplementation and type of questionnaire (Trabal et al, 2015), place of exercises (Sales et al, 2015), frequency (Santin-Medeiros et al, 2017), intensity (Santin-Medeiros et al, 2017), muscle strength (Haraldstad et al, 2017;Ni et al, 2016), and muscle mass (Haraldstad et al, 2017). Such variables should be studied in further research with older seniors, in order to expand the results identified so far.…”
Section: Relation Between Physical Exercise On the Quality Of Life Anmentioning
confidence: 99%
“…Taking into account the increase of life expectancy, researchers have been interested in studying the quality of life of the third age range, focusing on preserving and promoting the health and the well-being of this portion of the population so that they have a healthy aging (Fisken et al, 2015;Rachadel et al, 2015;Santin-Medeiros et al, 2017). According to the World Health Organization Quality of Life Group (WHOQOL, 1995), quality of life is the perception of individuals about their position in life combined with their sociocultural context and their objectives, expectancies, standards and concerns.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations